2019
DOI: 10.1111/mec.14993
|View full text |Cite
|
Sign up to set email alerts
|

Plumage microbiota covaries with the major histocompatibility complex in blue petrels

Abstract: To increase fitness, a wide range of vertebrates preferentially mate with partners that are dissimilar at the major histocompatibility complex (MHC) or that have high MHC diversity. Although MHC often can be assessed through olfactory cues, the mechanism by which MHC genes influence odour remains largely unclear. MHC class IIB molecules, which enable recognition and elimination of extracellular bacteria, have been suggested to influence odour indirectly by shaping odour‐producing microbiota, i.e. bacterial com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 131 publications
(188 reference statements)
3
65
1
Order By: Relevance
“…Many of the bacteria identified through molecular surveys in experiment 1 and through culture in experiment 2 have previously been identified as members of plumage or uropygial gland microbiota in other bird species. Staphylococcus was one of the most common bacteria found on blue petrel (Halobaena caerulea) plumage (Leclaire et al, 2019), and it has also been found on chicken (Gallus gallus), least auklet (Aethia pusilla) (Shawkey et al, 2006) and house finch (Carpodacus mexicanus) (Shawkey et al, 2003) feathers. Bacillus, Pseudomonas and Stenotrophomonas have been found on crested auklet (Aethia cristatella) (Shawkey et al, 2006) and eastern bluebird (Sialia sialis) plumage (Shawkey et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the bacteria identified through molecular surveys in experiment 1 and through culture in experiment 2 have previously been identified as members of plumage or uropygial gland microbiota in other bird species. Staphylococcus was one of the most common bacteria found on blue petrel (Halobaena caerulea) plumage (Leclaire et al, 2019), and it has also been found on chicken (Gallus gallus), least auklet (Aethia pusilla) (Shawkey et al, 2006) and house finch (Carpodacus mexicanus) (Shawkey et al, 2003) feathers. Bacillus, Pseudomonas and Stenotrophomonas have been found on crested auklet (Aethia cristatella) (Shawkey et al, 2006) and eastern bluebird (Sialia sialis) plumage (Shawkey et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The bluethroat has relatively few MHCI loci (i.e., four; O'Connor, Strandh, Hasselquist, Nilsson, & Westerdahl, 2016;Rekdal et al, 2018), which might be due to less exposure to intra-than extracellular pathogens (Minias et al, 2018) or some compensatory immunological mechanism (e.g., Gangoso et al, 2012;Star et al, 2011). Recent studies have identified a link between MHCII composition and individual odor in birds, possibly mediated through microbial communities and uropygial gland secretions (Leclaire et al, 2019(Leclaire et al, , 2014Leclaire, Strandh, Mardon, Westerdahl, & Bonadonna, 2017;Slade et al, 2016;Strandh et al, 2012). As there is growing evidence that birds are able to use olfaction in MHC-based mate choice, also in a selfreferencing manner (reviewed by Caro, Balthazart, & Bonadonna, 2015), MHCII is a prominent candidate for such a mate choice mechanism.…”
Section: Intermediate Not Maximized Mhcii Diversitymentioning
confidence: 99%
“…A great number of vertebrates have been observed to have high variation in MHC loci numbers, including fish [9,36], reptiles [37], birds [2,10,26], and mammals [15], which usually have more than one locus. For instance, three loci of MHC class I are expressed in Atlantic salmon [38], at least six loci are expressed in Blue tits [10], and 17 loci in a Cichlid species [39] but only two loci in Chinese sturgeon and paddlefish [9], as well as chickens [40].…”
Section: Discussionmentioning
confidence: 99%
“…A molecule of MHC class I consists of a microglobulin chain (β 2 m chain) and a heavy chain (α chain). This molecule connects peptides from intracellular pathogens and displays it at the surface of the cell where an immunoreaction is initiated upon recognition by CD8 + T cells [1][2][3]. The heavy chain that is encoded by classical MHC class I genes has a cytoplasmic region, a transmembrane region, and three extracellular domains designated α1, α2, and α3.…”
Section: Introductionmentioning
confidence: 99%